Cellular dynamics in pig-to-human kidney xenotransplantation - Wanqing Pan; Weimin Zhang; Binghan Zheng; Brendan Camellato; Jeffrey Stern; Ziyan Lin; Alireza Khodadadi‐Jamayran; Jacqueline Kim; Philip Sommer; Karen Khalil; Elaina Weldon; Jiangshan Bai; et al. (2024)
Xenotransplantation of genetically engineered porcine organs has the potential to address the challenge of organ donor shortage. Two cases of porcine-to-human kidney xenotransplantation were performed, yet the physiological effects on the xenografts and the recipients' immune responses remain largely uncharacterized.